Management of Pelvic Floor Disorder in a Diethylstilbestrol Daughter. Issue 3 (1st July 2017) - Chung, Christopher P.; Cao, Suzanne; Wakabayashi, Grace; Han, Ernest S.
Abstract : Between 1947 and 1971, the synthetic estrogen diethylstilbestrol (DES) was prescribed to pregnant women to prevent spontaneous abortions. Many studies have demonstrated adverse consequences of prenatal DES exposure. This report describes a DES daughter treated for uterine cancer who presented with a foreshortened vagina of 4 cm and stage III pelvic organ prolapse. She underwent successful vaginal native tissue reconstructive surgery with uterosacral colpopexy and anterior and posterior repair to lengthen her vagina and treat her prolapse. She then developed stress incontinence and underwent periurethral bulking 5 months later. She has been followed for 2 years with no recurrence of prolapse or incontinence.